Clinical trials of antiretroviral treatment interruption in HIV-infected individuals - Lau, Jillian S Y; Smith, Miranda Z; Lewin, Sharon R; McMahon, James H (AIDS (London), 2019)
: Despite the benefits of antiretroviral therapy (ART) for people living with HIV, there has been a long-standing research interest in interrupting ART as a strategy to minimize adverse effects of ART as well as to test interventions aiming to achieve a degree of virological control without ART. We performed a systematic review of HIV clinical studies involving treatment interruption from 2000 to 2017 to describe the differences between treatment interruption in studies that contained and didn't contain an intervention. We assessed differences in monitoring strategies, threshold to restart ART, duration and adverse outcomes of treatment interruption, and factors aimed at minimizing transmission. We found that treatment interruption has been incorporated into 159 clinical studies since 2000 and is increasingly being included in trials to assess the efficacy of interventions to achieve sustained virological remission off ART. Great heterogeneity was noted in immunological, virological and clinical monitoring strategies, as well as in thresholds to recommence ART. Treatment interruption in recent intervention studies were more closely monitored, had more conservative thresholds to restart ART and had a shorter treatment interruption duration, compared with older treatment interruption studies that didn't include an intervention.